DRAMATURGI PENGGUNA SECOND ACCOUNT DI MEDIA SOSIAL INSTAGRAM - Dito Yudhistira Iksandy (Universitas Teuku Umar, 2022)
Today, social media has become a self-representation and a form of existence for teenagers. One of the platforms that is currently popular is Instagram. These teenagers are aware that Instagram can affect their self-image, so in some cases they choose to share their stories and complaints with alternative Instagram accounts, in order to maintain their self-image. This study uses a qualitative method with a theoretical approach to Goffman's Dramaturgy. From the results of this study, it can be concluded that the informants created other Instagram accounts with the aim of being a place to complain, a place for collecting college assignments, and various other personal interests, because on their main account they use photos and their real names which are used as imaging.